2014
DOI: 10.1002/jnr.23345
|View full text |Cite
|
Sign up to set email alerts
|

Nonredundant function of two highly homologous octopamine receptors in food‐deprivation‐mediated signaling in Caenorhabditis elegans

Abstract: It is common for neurotransmitters to possess multiple receptors that couple to the same intracellular signaling molecules. This study analyzes two highly homologous G-protein-coupled octopamine receptors using the model animal Caenorhabditis elegans. In C. elegans, the amine neurotransmitter octopamine induces activation of cAMP response element-binding protein (CREB) in the cholinergic SIA neurons in the absence of food through activation of the Gq-coupled octopamine receptor SER-3 in these neurons. We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…3C-E). This is despite the observation that exogenous octopamine has been shown to inhibit pharyngeal pumping (27,56) and to be involved in food-dependent responses (60)(61)(62). This suggests that differences in assay may underlie the difference in function found for octopamine.…”
Section: Gaba and Dopamine Promote Pumping During Food Deprivationmentioning
confidence: 94%
“…3C-E). This is despite the observation that exogenous octopamine has been shown to inhibit pharyngeal pumping (27,56) and to be involved in food-dependent responses (60)(61)(62). This suggests that differences in assay may underlie the difference in function found for octopamine.…”
Section: Gaba and Dopamine Promote Pumping During Food Deprivationmentioning
confidence: 94%
“…The octopamine receptor, SER-3, is found on pharyngeal muscle (Carre-Pierrat et al 2006) and ser-3 mutants have a slightly lower pumping rate compared to N2 in the absence of food. SER-3 occurs on the cholinergic SIA neurons and is required for SIA activation upon food deprivation triggered by octopamine release from RIC neurons (Suo et al 2006;Yoshida et al 2014). However, the role of SIA neurons on feeding behaviour is not known.…”
Section: Octopamine/tyramine and Pharyngeal Pumpingmentioning
confidence: 99%
“…S8A). The ser-6 gene is expressed in a subset of head neurons, including the AWB olfactory neurons and the SIA interneurons (28,29). We found that restoring ser-6 function to ser-6 mutants either in all ser-6-expressing neurons, in AWB only, or in SIA only was sufficient to restore normal CO 2 attraction to starved animals (SI Appendix, Fig.…”
Section: Significancementioning
confidence: 79%